2007
DOI: 10.1021/jp064799y
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study on the Interaction of the Nitric Oxide Ions NO+ and NO- with the Side Groups of the Aromatic Amino Acids

Abstract: The interaction of the nitric oxide ions NO+ and NO- with benzene (C6H6) and the aromatic R-groups of the amino acids phenylalanine (Phe), tyrosine (Tyr), histidine (His), and tryptophan (Trp) have been examined using the DFT method B3LYP and the conventional electron correlation method MP2. In particular, the structures and complexation energies of the resulting half-sandwich Ar...NO+/- and sandwich [Ar...NO...Ar]+/- complexes have been considered. For the Ar...NO+ complexes, the presence of an electron rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…49 The Hirshfeld charge is a hypothetical ''promolecule'' with electron density Sq B and is constructed by the superposition of spherically symmetric charge densities Q The most noticeable change is in phenyl. The uniform charge distribution of benzene no more exists in phenyl, but all the carbon sites remain their negative charges except for C (1) (0.009 a.u.) which connects the aromatic ring with the alaninyl fragment.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The Hirshfeld charge is a hypothetical ''promolecule'' with electron density Sq B and is constructed by the superposition of spherically symmetric charge densities Q The most noticeable change is in phenyl. The uniform charge distribution of benzene no more exists in phenyl, but all the carbon sites remain their negative charges except for C (1) (0.009 a.u.) which connects the aromatic ring with the alaninyl fragment.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…1 Data mining projects have shown that amide-aromatic interactions of phenylalanine are highly essential in stabilization of protein residues over large configurational spaces. 2 It has been recognised 3 that the most populated conformer of L-phenylalanine (L-phe) in gas phase is stabilized by hydrogen bonds (Hbonds) which are enhanced by the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…12 Aromatic amino acids exhibit hydrophobic characteristics which play a vital role in many of the biological processes in the living cells. 13 L-Phenylalanine has received great attention both theoretically and practically. 5,[14][15][16][17] Recent data mining projects have shown that the amide-aromatic interactions of phenylalanine are highly essential in stabilization of protein residues over large configurational spaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, C-H bonds are also polarized, although to a lesser extent, and have been found to also be able to participate in hydrogen bonding [11]. Indeed, such interactions have been previously shown to be important in a variety of biological activities [12]. Hydrogen bonding plays a pivotal role in DNA structure and function.…”
Section: Introductionmentioning
confidence: 99%